Adjunctive Effects of a Sub-Antimicrobial Dose of Doxycycline on Clinical Parameters and Potential Biomarkers of Periodontal Tissue Catabolism - Emingil, Gülnur (Dent J (Basel), 2019)
Objectives: The aim of the present randomized, double-blind, placebo-controlled, parallel-arm study was to examine the effectiveness of a sub-antimicrobial dose of doxycycline (SDD) in combination with nonsurgical periodontal therapy, compared to nonsurgical periodontal therapy alone, on potential gingival crevicular fluid (GCF) biomarkers of periodontal tissue catabolism related to the clinical outcomes over a 12-month period. Materials and Methods: GCF was collected and clinical parameters were recorded from 30 periodontitis patients randomized either to an SDD or placebo group. The SDD group received SDD (20 mg) b.i.d for 3 months plus scaling and root planing (SRP), while the placebo group was given placebo capsules b.i.d for 3 months plus SRP. The patients were evaluated every 3 months during the 12-month study period. At each visit, clinical parameters and GCF sampling were repeated. Matrix metalloproteinase (MMP)-8, MMP-9, MMP-13, myeloperoxidase (MPO), osteoprotegerin (OPG), and tartrate-resistant acid phosphatase-5 (TRAP-5) were determined by IFMA and ELISA. Results: Significant improvements were observed in all clinical parameters in both groups over 12 months (p < 0.0125) while the SDD group showed significantly better reduction in gingival index (GI) and pocket depth and a gain in clinical attachment compared to the placebo group (p < 0.05). GCF MMP-8 and OPG levels significantly reduced in the SDD group compared to baseline (p < 0.05). GCF MMP-9 significantly decreased in both groups compared to baseline (p < 0.05). GCF MPO significantly decreased at 3 and 9 months in the SDD group, while it significantly decreased at 6 months in the placebo group (p < 0.05). TRAP and MMP-13 could be detected in none of the samples. Conclusions: The present results indicate that three months of adjunctive usage of SDD to nonsurgical periodontal therapy compared to nonsurgical periodontal therapy alone in periodontitis patients results in further improvement of clinical periodontal parameters and GCF markers of periodontal tissue breakdown over a 12-month period. Beneficial effects of adjunctive SDD therapy is likely to be related to the reduced levels of two major periodontitis-associated MMPs, MMP-8 and -9, and their potential oxidative activator MPO.